2021
DOI: 10.1109/tpds.2020.3019471
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Structured Divide-and-Conquer Algorithm for Symmetric Tridiagonal Eigenvalue Problems

Abstract: In this paper, a parallel structured divide-and-conquer (PSDC) eigensolver is proposed for symmetric tridiagonal matrices based on ScaLAPACK and a parallel structured matrix multiplication algorithm, called PSMMA. Computing the eigenvectors via matrix-matrix multiplications is the most computationally expensive part of the divide-and-conquer algorithm, and one of the matrices involved in such multiplications is a rank-structured Cauchylike matrix. By exploiting this particular property, PSMMA constructs the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The Divide-And-Conquer algorithm scales as [ 43 ], where n is the matrix dimension. The steps used in the Divide-And-Conquer eigensolver are summarized in the following algorithm (Algorithm 1) flowchart [ 42 ].…”
Section: Theory and Methodologymentioning
confidence: 99%
“…The Divide-And-Conquer algorithm scales as [ 43 ], where n is the matrix dimension. The steps used in the Divide-And-Conquer eigensolver are summarized in the following algorithm (Algorithm 1) flowchart [ 42 ].…”
Section: Theory and Methodologymentioning
confidence: 99%
“…Their study showed that ADC can be three times faster than DC. On the other hand, Liao et al [82] proposed a parallel structured divideand-conquer aiming to reduce the computational cost. Their method builds the local matrices by employing Cauchylike matrix generators without any communication and then reduces the computation costs by utilizing a structured lowrank approximation method.…”
Section: Steganalysismentioning
confidence: 99%
“…The DC algorithm [31] is easily parallelizable and has developed well in recent years [32,33]. However, efficient parallel implementations are not straightforward to program, and the decision to switch from task to data parallelism depends on the characteristics of the underlying machine.…”
Section: Introductionmentioning
confidence: 99%